(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Automation of Chromosome Analysis has long been considered a tedious task due to the partial occlusion of chromosomes. This calls for a non-trivial, dedicated procedure to segment chromosomes. In this paper, a new method is proposed which detects and separates occluded chromosomes, by separating out the chromosome cluster from the M-FISH image, followed by detecting the cut-points along which these clusters can be split into multiple regions. These regions are then combined into separate partial chromosomes based on difference matrix. After this stage the invisible regions due to occlusion is reconstructed based on the visibility in the five channels. The performance of the new proposalÂ Â was compared with the existing work and observed better performance in resolving occlusions. With 15 occludedÂ chromosome images tested, 90% accuracy was obtained